Imaging light-induced molecular fragmentation dynamics - Severt, Travis (Kansas State University, 2021)
When a molecule absorbs energy from its surrounding environment, the molecule's structure begins to evolve. Understanding this evolution at a fundamental level can help researchers, for example, steer chemical reactions to more favorable outcomes. The research reported in this thesis aims to further knowledge about molecular fragmentation dynamics using coincidence three-dimensional momentum imaging. To achieve this goal, we use a combination of ultrafast, intense laser pulses and vacuum-ultraviolet single-photon absorption to initiate and probe molecular dynamics. Specifically, ultrafast lasers allow researchers to follow and control molecular dynamics on their natural time scales. To complement such studies, we also use vacuum-ultraviolet single-photon absorption, in conjunction with the coincidence momentum imaging of all ejected fragments including electrons, to pinpoint state-selective dynamics occurring in various molecular targets. Throughout the thesis, we are interested in several different classes of molecular dynamics. First is the sequential fragmentation of molecules, where two or more bonds break in a step-wise manner. Specifically, we developed the native-frames analysis method, which is used to systematically reduce the dimensionality of multi-body fragmentation using the conjugate momenta of Jacobi coordinates. Applying this framework, we identify the signature of sequential fragmentation and separate its distribution from other competing processes. Moreover, we highlight the method's strengths by following fragmentation dynamics step-by-step and state-selectively using the single-photon double-ionization of D₂O as an example. In addition, we explore how the signature of sequential fragmentation within the native-frames method may change under different initial conditions and demonstrate the first steps toward expanding the method to four-body breakup using formic acid as an example. In the future, we hope to identify exotic sequential fragmentation pathways where two or more metastable intermediates are formed together. We also explore molecular isomerization and roaming dynamics leading to bond rearrangement. Specifically, we demonstrate that bond-rearrangement branching ratios in several triatomic molecules are approximately the same order of magnitude. Furthermore, we highlight that the formation of H₃⁺ in various alcohol molecules can occur via roaming of H₂ molecules. In addition, we study the coherent control of several molecular ions, demonstrating that the CS²⁺ molecule fragments via a pump-dump mechanism that occurs in a single laser pulse. We also explore the two-color control of D₂⁺ dissociation. Specifically, we observe phase shifts between pathways originating from different initial vibrational levels corresponding to "time-delays" of 10's of attoseconds, showing that such time-scales are not just accessible via electron dynamics. Since single vacuum-ultraviolet photon absorption experiments have proven to be powerful in studying molecular fragmentation dynamics, we investigate the enhancement of lab-based high-order harmonic generation photon sources driven by two-color laser fields. Specifically, we show that two-color 800-400-nm and 800-266-nm driving fields outperform the single-color 800-nm driver by more than an order of magnitude for the plateau harmonics. Furthermore, we demonstrate that the 800-266-nm bichromatic field can control the excursion time of an electron's trajectory by as much as a factor of 2. This result is important for techniques that use the rescattering electron wavepacket as a probe for molecular dynamics, such as in laser-induced electron diffraction (LIED) and high-harmonic spectroscopy (HHS) techniques. Finally, we highlight an upgrade of our coincidence three-dimensional momentum imaging method to measure breakup channels of molecular ions where the fragments have large mass-to-charge ratio differences. Specifically, we detect the light ions, such as H⁺ and H₂⁺, by adding a second movable offset detector closer to the interaction region. Meanwhile, the heavy ions and neutral fragments fly underneath the new detector and are measured using the original downstream detector, as demonstrated with preliminary CD₂⁺ measurements. In closing, this thesis covers a variety of topics with the common theme of better understanding molecular fragmentation dynamics, ranging from multi-body fragmentation dynamics to isomerization, roaming, and coherent control. In addition, we discuss enhancing high-harmonic-generation-based photon sources to help assist in such studies in the future. Overall, we believe the results presented throughout this thesis contribute to the advancement of molecular dynamics research.
Keywords: Atomic, molecular, and optical physics; Molecular fragmentation